The form and funtion as base for designing (2020)
We will begin for defining the origin of the form, since it is a fundamental part in the moment to be able to perceive the functions of a specific object. Secondly the own idea of function develops and as this one in turn, manages to be applied to an object and perceived by a user. On the other hand the definition of the materials appears and as these they managed to appear in a culture, later one speaks on the expectations, needs or hopes for that there looks a culture formed to a given and like that object we conclude with formal, functional definitions and aesthetics applied to a tea service.